2001
DOI: 10.1542/peds.108.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of Primary Care: Measuring Parents' Experiences of Pediatric Primary Care Quality

Abstract: The P3C is a practical, reliable, and valid measure of parents' reports of pediatric primary care quality. This brief measure could be used alone, or in conjunction with other measures, to enhance outcomes and evaluate the impact of systems changes on the delivery of the main elements of primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 25 publications
3
79
2
4
Order By: Relevance
“…Subscales of the PedsQL also demonstrated adequate to high internal consistency (a 5 .78-.89). Research has shown the usefulness of the PedsQL for clinical decision making (de Wit et al, 2008;Seid, Sobo, Gelhard, & Varni, 2004;Seid et al, 2001;Seid, Varni, Segall, & Kurtin, 2004), and the reliability and validity found within the present study provide evidence for the utility of the total score as a clinical measure within the IDD population and the utility of the subscales and total score for group level research within the population.…”
Section: Discussionsupporting
confidence: 65%
“…Subscales of the PedsQL also demonstrated adequate to high internal consistency (a 5 .78-.89). Research has shown the usefulness of the PedsQL for clinical decision making (de Wit et al, 2008;Seid, Sobo, Gelhard, & Varni, 2004;Seid et al, 2001;Seid, Varni, Segall, & Kurtin, 2004), and the reliability and validity found within the present study provide evidence for the utility of the total score as a clinical measure within the IDD population and the utility of the subscales and total score for group level research within the population.…”
Section: Discussionsupporting
confidence: 65%
“…Two of these investigations (93,104,105) indicate that factors other than financial resources drive health care utilization for farmworker children. In a series of analyses focused on child health services among farmworker families living along the U.S.-Mexico border, the Parent's Perceptions of Primary Care Measure (P3C) has been developed and validated (94,95). These same researchers (93) have reported on the use of health services for young children in farmworker families, finding that more than half the health care received by these children was received in Mexico.…”
Section: Research On Farmworker Health Servicesmentioning
confidence: 99%
“…However, knowledge of the health services needs of the farmworker population remains inadequate. Few studies have asked farmworkers about their health care needs and utilization or those of their families (exceptions include 95,104,105). Few data are available that evaluate the effectiveness of existing programs to improve health, health behaviors, or health services (exceptions include 38).…”
Section: Introductionmentioning
confidence: 99%
“…45 Another common barrier to integration is concern about disclosure of possible confidential information from the PCPs to the home visitors or vice versa. 43,46 Families may be apprehensive about disclosing information across services. Furthermore, there is concern that clinicians may be unprepared to act on family issues the home visitor may find in the home, and conversely, that home visitor may not be able to address the issues of PCP concern.…”
Section: Figurementioning
confidence: 99%